Correction to: Vegetation attributes drive the taxonomic richness and functional composition of beetles and spiders in mountainous urban green spaces - Frederick Gyasi Damptey; Bernard Fosu Frimpong; Daniel Kwame Debrah; Prince Pascal Agro; Edward Debrah Wiafe (Energy, Ecology and Environment, 2023)

Vegetation attributes drive the taxonomic richness and functional composition of beetles and spiders in mountainous urban green spaces - Frederick Gyasi Damptey; Bernard Fosu Frimpong; Daniel Kwame Debrah; Prince Pascal Agro; Edward Debrah Wiafe (Energy, Ecology and Environment, 2022)
Urban green spaces (UGS) enhance the quality of life in urban environments and serve as habitat corridors or refuge for organisms, including beetles and spiders. The attributes of UGS allow them to harbour species that offer essential ecosystem services. However, the ability of UGS to provide services is limited by the extent to which they have been altered anthropogenically. We described the taxonomic richness and functional composition of arthropods in a mountainous urban ecosystem of Ghana by focussing on the activity of both beetles and spiders at the family level. Two main land-use types (woodlands and built-up areas) were identified and characterised based on the presence or absence of certain vegetation attributes. Sixteen plots in each land-use type with sizes 20 × 20 m were demarcated and fitted with four pitfall traps in each plot to sample continuously for eight weeks, the activity density of both beetles and spiders. Samples were sorted into families and functional groups (detritivores, fungivores, herbivores and predators). The taxonomic richness and activity density were both significantly higher in the woodlands than in the built-up areas. Similarly, all functional groups showed a higher affinity to the woodlands than the built-up areas. Habitat attributes defined by plant diversity and structural complexity were the underlying drivers explaining the differences in arthropod communities between the land-use types. Though the built-up areas seem degraded and open, the remaining small vegetation patches still support the activities of some taxa that should merit the protection of such remnant vegetation in urban ecosystems.